2015
DOI: 10.1007/s11295-015-0844-3
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of garden rose architecture and its association with flowering behaviour

Abstract: International audience

Understanding the genetic basis of plant architecture is limited for woody plants due to the challenges of assessing the inheritance of their complex architecture. We aimed to evaluate the genetic variability of plant form and stature in a garden rose population, analyse the inheritance of plant architecture and its linkage with flowering behaviour and identify the quantitative trait loci (QTLs) controlling garden rose architecture. A total of 98 F 1 hybrids were derived from the cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 60 publications
2
9
0
1
Order By: Relevance
“…Plant height was found highly heritable with a moderate narrow-sense heritability (h 2 = 0.50) and high broad-sense heritability (H 2 = 0.82) ( Table 5). This finding was consistent with estimates reported previously by Gitonga et al (2014) (H 2 = 0.82), who measured this architectural component on potted tetraploid cut-flower rose populations, and by Kawamura et al (2015) (H 2 = 0.88), who studied the architecture of a small (98 individuals) diploid garden-rose population. Both studies reported broad-sense heritability only and have smaller populations and fewer families than our study.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Plant height was found highly heritable with a moderate narrow-sense heritability (h 2 = 0.50) and high broad-sense heritability (H 2 = 0.82) ( Table 5). This finding was consistent with estimates reported previously by Gitonga et al (2014) (H 2 = 0.82), who measured this architectural component on potted tetraploid cut-flower rose populations, and by Kawamura et al (2015) (H 2 = 0.88), who studied the architecture of a small (98 individuals) diploid garden-rose population. Both studies reported broad-sense heritability only and have smaller populations and fewer families than our study.…”
Section: Resultssupporting
confidence: 92%
“…Our results, combined with previous studies (Crespel et al, 2014;Kawamura et al, 2015) that reported high broad-sense heritability for several architectural traits of garden roses, indicated that rose plant architecture was a feasible target for rose breeding. Architectural traits with low narrow-sense heritability but moderately high to high broad-sense heritability, such as the number of primary shoots, the length of the primary shoot, and the number of nodes on the primary shoot, indicated important nonadditive effects.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…-OW population (151 individuals) was obtained from a cross between R. chinensis 'Old Blush' (OB), susceptible to BSD, and RW (Lopez Arias et al in press;Hibrand-Saint Oyant et al 2018;Soufflet-Freslon et al 2019), -HW population (209 individuals) was generated from a cross between a dihaploid rose named H190 (Meynet et al 1994), susceptible to BSD, and RW (Soufflet-Freslon et al 2019), -FW population (96 individuals) resulted from a cross between the cultivar 'The Fairy' (TF) and RW (Kawamura et al 2015). In the Earth-Kind® Trials using detached leaf assay, TF was shown to be susceptible to pathogen races 3, 8 and 9 (Zlesak et al 2010).…”
Section: Mapping Populationsmentioning
confidence: 99%
“…This primary structure was labeled in this study as the 'elementary architectural system'. Proximal axes sprouting at or under the substrate level, sometimes called 'renewal canes' (Zieslin and Mor, 1981) and empirically seen as total reiterated complexes (Costes et al, 2014;Kawamura et al, 2015) V o l u m e 8 3 | I s s u e 3 | J u n e 2 0 1 8 191 of an 'elementary architectural structure stage' (Crespel et al, 2013;Li-Marchetti et al, 2015), were denoted also as first branching order axes. These axes and all their descendants were further labeled as forming the 'delayed architectural systems'.…”
Section: Plant Acquisitionsmentioning
confidence: 99%